Challenges of Human Resource Management Towards Optimizing Public Service Performance in Realizing Sustainable Development at the Population and Civil Registration Service of Medan City - Kholilul Kholik; Mohammad Yusri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to analyze various obstacles and strategies in human resource management to improve the quality of sustainable public services. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. The results of the study indicate that the main challenges include limited human resource competencies, lack of work motivation, and inadequate infrastructure and technology systems. To overcome this, efforts are needed to increase human resource capacity through continuous training, implementation of an effective reward and punishment system, and modernization of information technology-based service systems. The conclusion of this study emphasizes that optimizing public service performance can be achieved through effective human resource management that is oriented towards sustainable development, so as to improve the quality of life of the community and support sustainable development goals (Sustainable Development Goals/SDGs) in Medan City.